Service Quality, Managerial Competence, and Library Facilities Affecting User Satisfaction at West Sumatra Provincial Library - Oktavia, Yelvi; Lanin , Dasman (Jurnal Administrasi dan Kebijakan Publik, 2025)
This study examines the factors influencing user satisfaction at the Regional Library of West Sumatra Province. Persistent user complaints regarding staff responsiveness, facility comfort, and declining engagement indicate service deficiencies that require systematic analysis. The study aims to assess how service quality, managerial interpersonal competence, and service facilities, both individually and collectively, affect user satisfaction. Using a quantitative approach with a survey method and proportionate stratified random sampling, data were collected from 392 users in 2024 and analyzed through multiple linear regression. The results show that all three variables have a positive and significant effect on user satisfaction. Service quality emerged as the most dominant predictor, followed by managerial interpersonal competence and service facilities. Together, these factors explain a substantial proportion of the variance in user satisfaction. The findings emphasize the practical need to enhance service quality, staff competence, and infrastructure while also strengthening the theoretical understanding of user-centered service delivery in public libraries. This study reaffirms the relevance of integrated service quality frameworks for improving user satisfaction and underscores the necessity for libraries to adapt to changing user expectations in the digital era.